Successful immunotherapy of autoimmune cholangitis by adoptive transfer of forkhead box protein 3+ regulatory T cells. (1st October 2014) - Tanaka, H; Zhang, W; Yang, G-X; Ando, Y; Tomiyama, T; Tsuneyama, K; Leung, P; Coppel, R L; Ansari, A A; Lian, Z X; Ridgway, W M; Joh, T; et al.
Summary: Treatment of primary biliary cirrhosis (PBC) has lagged behind that of other autoimmune diseases. In this study we have addressed the potential utility of immunotherapy using regulatory T cells (Treg ) to treat murine autoimmune cholangitis. In particular, we have taken advantage of our ability to produce portal inflammation and bile duct cell loss by transfer of CD8 + T cells from the dominant negative form of transforming growth factor beta receptor type II (dnTGF-βRII) mice to recombination-activating gene (Rag)1 –/– recipients. We then used this robust established adoptive transfer system and co-transferred CD8 + T cells from dnTGF-βRII mice with either C57BL/6 or dnTGF-βRII forkhead box protein 3 (FoxP3 + ) T cells. Recipient mice were monitored for histology, including portal inflammation and intralobular biliary cell damage, and also included a study of the phenotypical changes in recipient lymphoid populations and local and systemic cytokine production. Importantly, we report herein that adoptive transfer of Treg from C57BL/6 but not dnTGF-βRII mice significantly reduced the pathology of autoimmune cholangitis, including decreased portal inflammation and bile duct damage as well as down-regulation of the secondary inflammatory response. Further, to define the mechanism of action that explains the differential ability of C57BL/6 Treg versus  dnTGF-βRII Treg on the ability to down-regulate autoimmune cholangitis, we noted significant differential expression of glycoprotein A repetitions predominant (GARP), CD73, CD101 and CD103 and a functionally significant increase in interleukin (IL)-10 in Treg from C57BL/6 compared to dnTGF-βRII mice. Our data reflect the therapeutic potential of wild-type CD4 + FoxP3 + Treg in reducing the excessive T cell responses of autoimmune cholangitis, which has significance for the potential immunotherapy of PBC.